Analysis of Crude Oil Market Volatility and Macroeconomic Conditions: Empirical Evidence from Nigeria - Nuhu Musa (Review of Business and Economics Studies)
This study aims to investigate the relationship between the volatility of the crude oil market and the macroeconomic conditions in Nigeria. The author used the methods of the auto-regressive distributed lag (ARDL) model in conjunction with the generalized autoregressive conditional heteroscedasticity (GARCH) to determine the extent of volatility using a monthly dataset from January 2012 to December 2022. The author regressed the crude oil price volatility index on Organization of the Petroleum Exporting Countries (OPEC) production quotas, conflicts, GDP growth rate, exchange rate and inflation. The results indicate that oil price volatility relates negatively to GDP, implying that the volatility of crude oil prices dampens growth in Nigeria. The paper concludes that rising oil prices heighten inflation, depreciate the exchange rate and depress growth in Nigeria. To hedge against oil price volatility, the paper recommends that the Nigerian government adopt policy measures that would increase energy efficiency and reduce the country's dependency on oil exports through diversification in other related productive sectors such as agriculture and manufacturing.